Screening of mothers to detect Down syndrome: a practical approach in a resource limited setting - John, Shaji Thomas; Gayathri, Kizhanipurath (International Journal of Contemporary Pediatrics, 2022)
Background: Advanced maternal age, history of abortion and/or bleeding in pregnancy are risk factors for the birth of a chromosomally abnormal child. This study was done to find out their relationship especially in Down syndrome (DS). Methods: Retrospective observational study was done in children with DS and their mothers, from a major referral institution in India over a period of 20 years. The prevalence of abortion/bleeding in pregnancy with the age of mothers were analysed using statistical package for social sciences (SPSS) V20 software and compared in all the cytogenetic profiles. Results: In mothers less than 35 years 21.8% had abortion, 8% had bleeding and 4.5% had both abortion and bleeding. In mothers more than 35 years 25% had abortion, 7.3% had bleeding and 4% had both abortion and bleeding. Thus 34.5% had abortion/bleeding in mothers less than 35 years and 36.8% in those above 35 years. 15.25% mothers were more than 35 years. When the individual cytogenetic pattern and the prevalence of abortion/bleeding were analysed in maternal age group less than 35 years; a higher prevalence was seen in the non-disjunction group (34.2%), followed by translocation (24%) and mosaic (21.42%). In maternal age group >35 years prevalence was high, though not statistically significant, in the mosaic group (66.67%) followed by non-disjunction (43%). Conclusions: Mothers with a history of abortion/bleeding and those above 35 years constituted 44.7%. Ideally all pregnant women should be screened for chromosomal aneuploidies, but in resource limited countries screening should be done at least in the above noted high risk groups.